2021
DOI: 10.1080/09553002.2021.1876955
|View full text |Cite
|
Sign up to set email alerts
|

Low- and moderate-dose non-cancer effects of ionizing radiation in directly exposed individuals, especially circulatory and ocular diseases: a review of the epidemiology

Abstract: Purpose: There are well-known correlations between high and moderate doses (>0.5 Gy) of ionizing radiation exposure and circulatory system damage, also between radiation and posterior subcapsular cataract. At lower dose correlations with circulatory disease are emerging in the Japanese atomic bomb survivors and in some occupationally exposed groups, and are still to some extent controversial. Heterogeneity in excess relative risks per unit dose in epidemiological studies at low (<0.1 Gy) and at low-moderate (>… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(38 citation statements)
references
References 185 publications
0
34
0
2
Order By: Relevance
“…Some non-cancer effects might be better classified as stochastic effects. Evidence for increased risk of diseases of the circulatory system following exposure to ionising radiation at low to moderate doses and dose-rates has accumulated from epidemiological studies over the recent decade (Azizova et al 2015 ; Tapio et al 2021 ; Little et al 2021 ). These results show an increase in the probability of occurrence with dose, with no variation in severity.…”
Section: Research To Support Radiation Risk Assessmentmentioning
confidence: 99%
“…Some non-cancer effects might be better classified as stochastic effects. Evidence for increased risk of diseases of the circulatory system following exposure to ionising radiation at low to moderate doses and dose-rates has accumulated from epidemiological studies over the recent decade (Azizova et al 2015 ; Tapio et al 2021 ; Little et al 2021 ). These results show an increase in the probability of occurrence with dose, with no variation in severity.…”
Section: Research To Support Radiation Risk Assessmentmentioning
confidence: 99%
“…The monitoring of populations exposed to low-dose radiation is important but conclusions should be made with caution considering known and unknown bias. For example, "the very high rates of circulatory disease" [66] in some nuclear worker cohorts from the former Soviet Union are probably caused by habitual overdiagnosis of cardiovascular diseases in unclear cases, which is a known confounder [67]. Reliable evidence in regard to biological effects of low radiation doses can be obtained in extensive animal experiments rather than in epidemiological studies.…”
Section: Clinical and Medical Case Reportsmentioning
confidence: 99%
“…Since then, it has widely been considered that ionizing radiation induces such secondary glaucoma (neovascular glaucoma in particular) following high-dose fractionated radiotherapy (e.g., >40 Gy delivered in 2-Gy fractions) [7,8]. In contrast, no significantly increased radiation risk was observed for primary glaucoma, POAG or PACG in several exposed cohorts [9][10][11][12][13][14] until recent studies in Japanese atomic bomb survivors suggested a significantly increased risk for NTG following acute radiation exposure at doses much lower than radiotherapeutic doses [9,10]. This introduces the possibility that radiation exposure induces NTG and raises a question whether such induction depends on dose and dose rates.…”
Section: Introductionmentioning
confidence: 99%